Taming the parent oxoborane - Kundu, Gargi; Amrutha, P. R.; Raj, K. Vipin; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Chemical Science, 2023)
Despite recent advancements in the chemistry of multiply bound boron compounds, the laboratory isolation of the parent oxoborane moiety, HBO has long remained an unsolved and well-recognized challenge. The reaction of 6-SIDipp(.)BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl)tetrahydropyrimidine2-ylidene] with GaCl3 afforded an unusual boron-gallium 3c-2e compound (1). The addition of water to 1 resulted in the release of H-2 and the formation of a rare acid stabilized neutral parent oxoborane, LB(H)]O (2). Crystallographic and density functional theory (DFT) analyses support the presence of a terminal B=O double bond. Subsequent addition of another equivalent of water molecule led to hydrolysis of the B-H bond to the B-OH bond, but the `B=O' moiety remained intact, resulting in the formation of the hydroxy oxoborane compound (3), which can be classified as a monomeric form of metaboric acid.